Ketogenic diet therapy is effective in encephalitis with refractory seizures. (October 2014) - Matsuzono, Kosuke; Kurata, Tomoko; Deguchi, Shoko; Yamashita, Toru; Deguchi, Kentaro; Abe, Koji
<x content-type="archive" xml:space="preserve">Abstract</x> Objective and importance: Although ketogenic diet therapy is effective in refractory seizures in childhood, its effect on adult encephalitis with similar refractory seizures and prolonged encephalopathy has not been well reported. Clinical presentation: We report here a case of a 22-year-old man with acute encephalitis with refractory repetitive partial seizures (AERRPS). Intervention: Partial seizures of the face developed to repeated generalized convulsions, which were refractory against anti-epileptic drugs and a high dose of propofol. After struggling for 9 months, he dramatically recovered after ketogenic diet therapy. Conclusion: Ketogenic diet therapy may be an important tool to help cure AERRPS.